MENINGKATKAN PENGENALAN ANGGOTA TUBUH BAGIAN ATAS MELALUI BERNYANYI PADA ANAK TUNAGRAHITA SEDANG - Yetti - Suheri (Universitas Negeri Padang, 2012)
This research of class activity purpose to know and to make the result of study high to learn science throw singing. Objects of this reasearch is teaching and learning activity on science subjects. The sources of this reasearch are teachers, friends and also 3 of students grade I elementary school (SLB-C) in Payakumbuh. The result of this research shows thats there are improving of students learning activity throw that method in other hand, learning and teaching activity throw singing very goood and can also use in learning process of science grade I elementary school (SLB-C) in Payakumbuh.